The Effect of Service Quality, Company Image, And Experiental Marketing On Consumer Loyalty of Ace Hardware BG Junction Surabaya - Chairul Huda; Novelia Asita Mranani; Supartini (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
The purpose of this study is to determine the effect of Service Quality, Company Image and Experiential Marketing on Consumer Loyalty of ACE Hardware BG Junction Surabaya simultaneously and partially. The analysis technique uses Multiple Regression Test (multiple regression) with the SPSS program. The results showed that the variables of service quality, company image and experiential marketing had a joint or simultaneous effect on customer satisfaction at ACE Hardware at BG Junction Surabaya. For Service quality has a positive and significant influence on customer satisfaction. Company image does not have a positive and significant effect on customer satisfaction. Experiential marketing has a positive and significant influence on customer satisfaction.